2023
DOI: 10.1007/s12223-023-01078-4
|View full text |Cite
|
Sign up to set email alerts
|

Application and effectiveness of Methylobacterium symbioticum as a biological inoculant in maize and strawberry crops

Abstract: The effectiveness of Methylobacterium symbioticum in maize and strawberry plants was measured under different doses of nitrogen fertilisation. The biostimulant effect of the bacteria was observed in maize and strawberry plants treated with the biological inoculant under different doses of nitrogen fertiliser compared to untreated plants (control). It was found that bacteria allowed a 50 and 25% decrease in the amount of nitrogen applied in maize and strawberry crops, respectively, and the photosynthetic capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…It remains to be better clarified whether the selected strain of M. symbioticum used in this study is more effective in N fixation than others under such diverse conditions. The results of this study showed that in lettuce, under these cultivation conditions, the N fixed by the microorganism was very modest, not matching the very favourable results reported in maize and strawberries by the team that developed the commercial product [28,39]. The observed N fixation values in this study were so low (<6.3 kg ha −1 at the highest N rate) that they would hardly justify farmers' application of this commercial product.…”
Section: Effect Of the Inoculant On Dry Matter Yield And Apparent Nit...contrasting
confidence: 79%
See 2 more Smart Citations
“…It remains to be better clarified whether the selected strain of M. symbioticum used in this study is more effective in N fixation than others under such diverse conditions. The results of this study showed that in lettuce, under these cultivation conditions, the N fixed by the microorganism was very modest, not matching the very favourable results reported in maize and strawberries by the team that developed the commercial product [28,39]. The observed N fixation values in this study were so low (<6.3 kg ha −1 at the highest N rate) that they would hardly justify farmers' application of this commercial product.…”
Section: Effect Of the Inoculant On Dry Matter Yield And Apparent Nit...contrasting
confidence: 79%
“…Also, the nitrate content in the tissues, sometimes seen as an indicator of high sensitivity to N availability because it is an unmetabolized form that accumulates in tissues [38], varied similarly to the total N concentration in the leaves (Figure 3). Thus, this variable also did not reveal any influence on the plant's N nutritional status due to the microorganism application, perhaps because in biological fixation, the plant accesses N in the form of ammonia [12,13,28].…”
Section: Effect Of the Inoculant On Dry Matter Yield And Apparent Nit...mentioning
confidence: 94%
See 1 more Smart Citation